2021
DOI: 10.3390/su13031272
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Public Sector Choice: Perceptions and Motivational Determinants at the Pre-Entry Level

Abstract: The 2030 Agenda for Sustainable Development now guides public administrations in conveying all their functions. The 17 Sustainable Development Goals (SDG), directly or indirectly, need effective public services and officials for successful implementation. Although working in public entities has been related to ‘a sense of duty and morality’, literature reports that motivation and sense of self-worth among public officials have been declining for many years, which in turn can endanger their performance, diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(45 reference statements)
0
7
1
Order By: Relevance
“…Quite the contrary, our respondents felt more attracted to public organizations and also rated their prestige as higher than the prestige of private employers. This finding is contradictory to a number of studies that found the opposite effect (Erlanger et al, 1996; Fowler & Birdsall, 2020; Pedersen, 2013; Santinha et al, 2021; Van de Walle et al, 2015). It should be noted, however, that these studies differ strongly in the sampled target groups of public sector recruitment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Quite the contrary, our respondents felt more attracted to public organizations and also rated their prestige as higher than the prestige of private employers. This finding is contradictory to a number of studies that found the opposite effect (Erlanger et al, 1996; Fowler & Birdsall, 2020; Pedersen, 2013; Santinha et al, 2021; Van de Walle et al, 2015). It should be noted, however, that these studies differ strongly in the sampled target groups of public sector recruitment.…”
Section: Discussioncontrasting
confidence: 99%
“…Pedersen (2013) finds a similar distribution among bachelor and master students of economics, political science, and law at two Danish universities who were asked for their sector preferences after graduation, all job characteristics being equal. Santinha et al (2021) report that a clear majority of students across a broad range of subjects at a Portuguese university prefer employment in the private sector over the public and nonprofit sector when asked for their future career intentions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The results point to a deterioration of working conditions, but academics maintain a positive view regarding the academic profession. Santinha et al (2021) state that the adaptation of the private sector management style to public administration has had a crucial impact in the field of human resources, the most representative being the loss of historically attractive characteristics in the public sector, such as the guarantee of job security and predictability in promotions.…”
Section: Portuguese Public Administration Reform and New Public Managementmentioning
confidence: 99%
“…It follows that less motivated public officials will be less committed to their organisations, including in Portugal, even after the changes put into effect after the 1980s (Santinha et al 2021). The literature (Santinha et al 2021) suggests that the objective of attaining job stability may perhaps not be a fulfilling career choice. Our research is in line with these findings.…”
Section: Conclusion and Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation